Reforma al régimen de sanciones por la violación de las normas de libre competencia en Colombia: Análisis de la ley 2195 de 2022 - Miranda Londoño, Alfonso (2023)
This paper contains a detailed analysis of the reforms introduced by Ley 2195/2022 into antirust regulation in Colombia. For this purpose, the background of Ley 2195 of 2022 is analyzed in detail, which is a transparency and anti-corruption law, that was modificated in the sanctions regime contained in Ley 1340 of 2009. In this regard, we made a critical assessment of the increase of the sanctioning capacity for the performance of restrictive practices of competition and the way in which such power has evolved since the publication of Ley 155 of 1959 until today.